15 Development of a digital self-care management application for children with nephrotic syndrome: my nephrotic notebook. (22nd November 2019) - Archer, Thomas; Gray, Hugh; Tsang, Wing Ping; Bassi, Daiana; Conner, Sue; Fu, Yun; Mohamedally, Dean; Molyneux, Gemma; Roberts, Graham; Sebire, Neil; Webb, Hazel; Hothi, Daljit
Abstract : Introduction: Children with Nephrotic Syndrome need to monitor their condition by logging their urine protein levels daily (proteinuria). Currently, this relies on patients keeping a paper diary that can be difficult to interpret. The aim of this project was to develop a mobile app to enhance the user experience, and to make the process more engaging for children. In addition, the implementation of a digital process would allow data to be presented clearly, improving the ability of the clinical care team to view data collected, and easily identify patients whose condition is unstable. Methods: As part of a joint collaboration between GOSH and UCL computer science (CS) through the industry exchange network programme, a mobile app was developed to allow easy recording of proteinuria dipstick readings in relation to disease management guidance. The application front-end was developed in Ionic4 that uses standard web technologies; HTML, CSS and JavaScript. The back-end consists of an internal SQLite Database that provides the mobile app with direct read and write access to the data, which is stored locally in a single file. Results: The app allows users to easily input their daily protein urea reading. The reading can be viewed on a calendar to show readings over time. Data is presented in a way that allows easy visualisation and identification of the days when readings are higher than the normal range, data recorded can be exported into the patient record. In addition, the clinical care team can upload the patient's treatment plan to the app, providing the patients with an electronic record of the plan they should follow if relapse occurs, information that is normally provided in paper form. Conclusion: A mobile app to allow patients to report home test results has been developed with potential for expansion across a range of clinical services.